The Application of Non-Thermal Plasma and Electrocoagulation as Purifier of Liquid Waste in Home Industries - Lisa Samura; Mustamina Maulani; Cahaya Rosyidan; Valentinus Galih Vidia Putra (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2022)
This study aims to examine the decomposition method of liquid waste in the home industry, especially in the tofu industry, by using non-thermal plasma and electrocoagulant methods that are environmentally friendly and with low energy. In this study, the plasma method, electro-coagulant method, and a combination of both (electro-coagulant followed by plasma method and plasma followed by electro-coagulant method) were used to decompose liquid waste in the tofu industry. The results showed that non-thermal plasma followed by the electrocoagulation method was the most effective in reducing the T.D.S. value of 1983 ppm (the minimum value of the total control T.D.S. was around 2702 ppm), the minimum value of electrical conductivity (E.C.) was around 3967 (μs/cm), and also obtained a value of 3967 (μs/cm). pH 7.0. Based on the research results, non-thermal plasma combined with the electrocoagulant method can be applied to more optimally decompose liquid waste, especially in the tofu industry. The combination method of plasma and electrocoagulation to decompose the tofu industrial wastewater, which is environmentally friendly, is the novelty of this research